(untitled) (Bangladesh Journal of Agricultural Research, 2011)
A field experiment was conducted to determine the sensitivity of wheat to water stress and changes in water relations and yield of wheat (Triticum aestivum L.) under water stress conditions applied at different growth stages. The experiment comprised of two wheat cultivars and four water stress treatments, maintained by withholding water at tillering, anthesis, and at both stages. Water stress caused reduction in leaf relative water contents, water potential, osmotic potential, turgor potential, growth and yield components of both the wheat cultivars. The results indicated that high value of relative water contents were associated with increased yield and yield components. Consecutive stresses at both growth stages caused severe reduction in yield and yield components in both cultivars of wheat. Keywords: Water stress; water relations; growth; Triticum aestivum; yield components. DOI: http://dx.doi.org/10.3329/bjar.v36i3.9264 BJAR 2011; 36(3): 455-468